The Effect of Interpersonal Communication and Teacher Competence on the Quality of Character Education and Student Learning Achievement - Habibie Yusuf; Muhibbin Syah; M Ali Ramdhani; Aan Hasanah (International Journal of Nusantara Islam, 2020)
MTsN 01 Kota Gorontalo and MTsN 01 Bone Bolango are educational institutions that focus on character development and have programs that can shape the character of their students. The results showed that: First, interpersonal communication has a positive and significant effect on the quality of character education at MTsN 01 Kota Gorontalo and MTsN 01 Bone Bolango. Second, Teacher Pedagogic Competence has a positive and significant effect on the Quality of Character Education at MTsN 01 Kota Gorontalo and MTsN 01 Bone Bolango. Third, interpersonal communication and teacher pedagogic competence together have a positive and significant effect on the quality of character education at MTsN 01 Kota Gorontalo and MTsN 01 Bone Bolango. Fourth, Interpersonal Communication has a positive and significant effect on Student Learning Achievement. Fifth, Teacher Pedagogic Competence has a positive and significant effect on Learning Achievement at MTsN 01 Kota Gorontalo and MTsN 01 Bone. Sixth, interpersonal communication and teacher pedagogical competence together have a positive and significant effect on learning achievement at MTsN 01 Kota Gorontalo and MTsN 01 Bone Bolango.